Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik pada PT. Dinda Holding Company (DHC) Menggunakan Metode Simple Additive Weighting (SAW) - Bintang Dea Apriliansyah; Aan Risdiana; Achmad Birowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The problem faced by PT. Dinda Holding Company (DHC) is that it has difficulty in determining the best employees from a number of employees with varying performance qualities. Until now, the selection process has been carried out manually, taking into account the subjective assessments of the owner or store manager, without a structured evaluation system. As a result, employee selection tends to be inconsistent and leads to dissatisfaction among both employees and the business owner. Additionally, selected employees do not always demonstrate optimal performance, which impacts service quality and the operational sustainability of the store. Therefore, a decision support system was designed to assist PT. Dinda Holding Company (DHC) in selecting the best employees objectively, quickly, and accurately. Employees are human resources used as a driving force in the business operations of a company. The company faces the challenge of maintaining its competitive edge, which requires data on the performance of employees with good performance. This system applies the Simple Additive Weighting (SAW) method to perform calculations and evaluations based on predetermined criteria. The result of this system development is a desktop-based application using the Java programming language and a MySQL database, which is expected to assist management in making more measurable and structured decisions.